Pet Reptiles: A Potential Source of Transmission of Multidrug-Resistant Salmonella - Marin, Clara; Lorenzo-Rebenaque, Laura; Laso, Omar; Villora-Gonzalez, José; Vega, Santiago (Frontiers in Veterinary Science, 2021)
Salmonella spp. is widely considered one of the most important zoonotic pathogens worldwide. The close contact between reptiles and their owners provides favourable conditions for the transmission of zoonotic pathogen infections, and approximately 6% of human salmonellosis cases are acquired after direct or indirect contact with reptiles. Moreover, antimicrobial resistance is one of the most important health threats of the 21st century and has been reported in Salmonella strains isolated from pet reptiles, which could entail therapeutic consequences for their owners and breeders. The aim of this study was to assess Salmonella carriage by pet reptiles in pet shops and households, and their role in the transmission of antimicrobial resistance, to inform the owners about the possible risks factors. During the period between January 2019 and December 2019, 54 reptiles from pet shops and 69 reptiles from households were sampled in the Valencian Region (Eastern Spain). Three different sample types were collected from each reptile: oral cavity, skin and cloacal swabs. Salmonella identification was based on ISO 6579-1:2017 (Annex D), serotyped in accordance with Kauffman-White-Le-Minor technique, and antibiotic susceptibility was assessed according to Decision 2013/652. The results of this study showed that 48% of the pet reptiles examined from households and pet shops carry Salmonella spp. All the strains isolated presented resistance to at least one antibiotic, and 72% were multidrug-resistant strains, the most frequently observed resistance patterns being gentamicin-colistin and gentamicin-colistin-ampicillin. The present study demonstrates that pet reptiles could be a source of human multidrug-resistant Salmonella infection. In this context, the most optimal prevention of multidrug-resistant Salmonella infections necessarily involves strict control of the sanitary status of reptile pet shops and hygienic handling by the individual owners at home.